Treatment terminations during radiation therapy: A retrospective descriptive single-center analysis - Alaattin Ozen; Ilknur Harmankaya; Canan Ozdemır; Mehmet Halıcı; Oya Coskun; Ekin Baran Guler; Ozge Atılla; Sumeyra Can (PLoS ONE, 2026)
Background Radiotherapy (RT) is a cornerstone of cancer management, substantially improving local tumor control and overall survival. However, a subset of patients fail to complete the prescribed RT course. Identifying the factors associated with treatment termination is essential to enhancing cancer care delivery and patient outcomes. Methods This retrospective, single-center analysis included 10039 patients who underwent RT between January 2020 and December 2024. Patients who terminated treatment before completion were identified in institutional RT records. Demographic and clinical characteristics, treatment intent, and reasons for termination were primarily evaluated using descriptive statistical analyses, with exploratory comparative analyses performed between curative- and palliative-intent groups. Results Between 01/01/2020 and 12/31/2024, RT was terminated in 297/10039 patients (2.96%). The most leading causes of termination was deterioration in performance status (143 patients, 48.1%). Of these, 170 patients (57.2%) had been treated with palliative intent. Lung cancer (96 patients, 32.3%) was the most frequent primary diagnosis, while the brain (92 patients, 31%) was the most commonly irradiated site. The median number of prescribed fractions was 13 (range: 2–44), and patients completed a median of 51.6% (range: 5–93%) of these fractions before termination. The most common reason was deterioration in performance status (48.1%). Treatment termination rates were significantly higher in palliative cases compared with curative cases (6.13% [170/2,772] vs. 1.75% [127/7,267]; χ² = 134.4; p < 0.001). Relative risk analysis indicated that palliative-intent patients had a 3.50-fold higher risk of treatment termination. Performance deterioration was more frequent in the palliative group (72.4% vs. 27.3%; p < 0.001). Treatment-related toxicity (grade III-IV) occurred predominantly in curative-intent patients (88.9% vs. 11.1%; p < 0.001). Conclusion Most RT terminations occurred among patients with poor performance status and advanced disease. These findings suggest that multidisciplinary supportive care may be relevant and should be evaluated in future prospective studies.